2016
DOI: 10.5513/jcea01/17.1.1664
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a phytogenic additive on nutritional composition of turkey meat

Abstract: The aim of the study was to analyze the effect of a blend of phytogenic additive on nutritional and mineral composition of breast, thigh muscles and liver in fattening turkeys. A total 300 female turkeys were monitored in the trial. 1-day old broadbreasted white turkeys hybrid XL were randomly divided into two groups (150 pcs per each). Turkeys in control group were fed by standard diet for fattening and in experimental group from the 1st to the 12th week by complete feed mixture with supplementation of a blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…The fruits have also been used to make wine, brandy, white wine vinegar and beer (Bartram, 1772;Briand, 2005). Additionally, the by-products from processing persimmon fruits or leaves can be used in animal nutrition as a source of bioactive compounds Herkeľ et al, 2016) and thereby improve the performance of farm animals.…”
Section: Introductionmentioning
confidence: 99%
“…The fruits have also been used to make wine, brandy, white wine vinegar and beer (Bartram, 1772;Briand, 2005). Additionally, the by-products from processing persimmon fruits or leaves can be used in animal nutrition as a source of bioactive compounds Herkeľ et al, 2016) and thereby improve the performance of farm animals.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dietary plant extracts added into feed mixture of layers on the content of phosphorus, calcium and magnesium in eggshell were not significant (Lokaewmanee et al, 2014). Herkeľ et al (2016) also reported that phytogenic additive including essential oil may significantly affect mineral composition in poultry products. Feeding olive oil along with conjugated linoleic acid completely prevented changes in the mineral content of eggs (Aydin et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Interactions in the content of nutrients in the animal organisms depend on the species, breed, sex, rearing system, health status, and the physiological-biochemical function of muscles and organs [ 47 49 ]. The interrelations between nutrients in the organism are strongly influenced by their content and availability in the diet as well as the status of the gastrointestinal microbiome, which can be optimized by application of appropriate dietary additives [ 5 , 10 , 50 , 51 ]. In the investigations conducted by Herkel et al [ 5 ], significant correlations were found between dry matter with crude protein and fat in breast and thigh muscles of fattening turkeys fed with a diet supplemented with a blend of essential oils from origanum, anise, and citrus fruits and fructooligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, phytobiotics increase the bioavailability of some micro- and macroelements, which are accumulated in tissues more easily. For instance, increased contents of Mg, Zn, and Cu were detected in poultry breast and thigh meat and in the liver [ 2 5 ]. Still, the poultry industry is seeking new nutrition solutions that can ensure a high level of production, which is inextricably associated with maintenance of a good health status of chickens throughout the feeding period.…”
Section: Introductionmentioning
confidence: 99%